Zotos, Yorgos - (:unkn) unknown (My University, 2026)
Yorgos Zotos, is currently Professor at the Department of Communication and Internet Studies, Cyprus University of Technology. He holds a Bachelor’s Degree from University of Macedonia, Thessaloniki, Greece, an MBA from University of Minnesota, Minneapolis, USA and a Ph.D. from Aristotle University of Thessaloniki, Greece. He has taught at Aristotle University and University of Macedonia, Thessaloniki, Greece, Rhode Island University and University of Pennsylvania, Wharton Business School, USA, and University of Canterbury in New Zealand. Yorgos Zotos has published articles in refereed and indexed international journals and participated in international conferences of marketing and communication. His research work has been cited in international refereed journals. He is reviewer in various international journals. He is presently serving as a member of the Editiorial Board to International Journal of Advertising. Yorgos Zotos has also published a text-book, research monographs and articles in reading books. He was research coordinator and principal researcher in various research programs funded by the Greek Ministry of Education and European Union. He served for two terms as Head School of Economics, for ten years as Head Department of Business Administration and seven years as Director of Graduate Studies, School of Economics, Aristotle University of Thessaloniki. He also served as Associate-Head of Institute of Communication, Athens, Greece. Yorgos Zotos is a member of the Greek, European and American Academies of Marketing and member of International Society of Marketing and Development.